2022
DOI: 10.1021/jacsau.2c00345
|View full text |Cite
|
Sign up to set email alerts
|

Can Second Coordination Sphere and Long-Range Interactions Modulate Hydrogen Atom Transfer in a Non-Heme Fe(II)-Dependent Histone Demethylase?

Abstract: Fe(II)-dependent oxygenases employ hydrogen atom transfer (HAT) to produce a myriad of products. Understanding how such enzymes use dynamic processes beyond the immediate vicinity of the active site to control the selectivity and efficiency of HAT is important for metalloenzyme engineering; however, obtaining such knowledge by experiments is challenging. This study develops a computational framework for identifying second coordination sphere (SCS) and especially long-range (LR) residues relevant for catalysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 74 publications
(207 reference statements)
0
27
1
Order By: Relevance
“…The hydrogen bonds have been estimated through a Python script . Quite surprisingly, it is observed that certain hydrogen bonds are preserved among the different mutations, which contrasts earlier studies that reported notable deviations in the presence of hydrogen bonds among different mutations , …”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The hydrogen bonds have been estimated through a Python script . Quite surprisingly, it is observed that certain hydrogen bonds are preserved among the different mutations, which contrasts earlier studies that reported notable deviations in the presence of hydrogen bonds among different mutations , …”
Section: Resultscontrasting
confidence: 99%
“…The hydrogen bonds have been estimated through a Python script. 71 Quite surprisingly, it is observed that certain hydrogen bonds are preserved among the different mutations, which contrasts earlier studies that reported notable deviations in the presence of hydrogen bonds among different mutations 72,73 The influence of the mutations on the intermolecular distances relevant for the cascade of electron transfers (d 1−4 ) (see Figure 1) has been summarized in Figure 8. Figure 8 shows that the introduced mutations do not significantly affect the intermolecular distances between the tryptophans.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…The second coordination sphere (SCS) and protein environment in general are largely involved in enzyme catalysis [25,28–32] . The focus of this study is to explore the specific interactions in the SCS and beyond that control the dioxygen transport and binding in two Fe II /2OG enzymes – PHF8, which uses the in‐line mode, and EFE, which implements exclusively the off‐line mode.…”
Section: Introductionmentioning
confidence: 99%
“…The second coordination sphere (SCS) and protein environment in general are largely involved in enzyme catalysis. [25,[28][29][30][31][32] The focus of this study is to explore the specific interactions in the SCS and beyond that control the dioxygen transport and binding in two Fe II /2OG enzymes -PHF8, which uses the in-line mode, and EFE, which implements exclusively the off-line mode. Here, we use computational methods to investigate whether the dioxygen binding and interactions with SCS residues in Fe II / 2OG oxygenases to determine the formation of either an in-line or off-line Fe III -OO *À Intermediate, which further influences their reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…74 The 2-oxoglutarate (2OG) dependent non-haem iron oxygenases catalyse a wide variety of oxidative processes and have been the target of multiple recent studies. [75][76][77][78][79][80][81][82][83][84][85][86] Chaturvedi et al used ChemShell QM/MM calculations to investigate the reaction mechanism of PHF8, which catalyses demethylation of methylated lysine in histones, and is a target for cancer treatments. 87 The simulations revealed that rearrangement of 2OG at the iron centre is an important part of the mechanism, which may help inform the design of inhibitors.…”
Section: Qm/mm Simulations Of Biomoleculesmentioning
confidence: 99%